Cut-off values of one-minute sit-to-stand test for determining physical performance in mild-post-COVID-19 individuals - Arunrat Srithawong; Puttipong Poncumhak; Tichanon Promsrisuk; Patchareeya Amput (Canadian Journal of Respiratory Therapy)
# Background